development of e-modules based on brain balance to improve students' mathematical creative thinking skills on geometric sequences and series material - Fatmawati, Vera; Adiastuty, Nuranita; Nurhayati, Nunu (Jurnal of Math Tadris, 2023)
This research aims to describe the process of developing an e-module based on brain balance to improve students' mathematical creative thinking abilities on geometric sequences and series. The development of this e-module uses the Whole Brain Teaching (WBT) method, which is a brain balance method. The applications used in e-module development are Microsoft Office Word and Flip PDF Professional. This research is development research (Research and Development). The development model used in this research is the Plomp model which consists of three phases, namely the Preliminarity Phase, the Development or Prototype Phase, and the Assessment Phase. The instruments used in this research are validation sheets, practicality sheets and the N Gain Test instrument to see the effectiveness of the e-module. Based on the results of validation tests carried out by six media and material expert validators, the average score was 94.77% and was categorized as very valid. Meanwhile, based on the results of the e-module practicality test conducted on teachers and students, the average score was 91.3% and was categorized as very good. Based on the N Gain test carried out in class e-module is categorized as medium.